'Modernism' and the Ethiopian Orthodox Sunday School Movement: Indigenous Movements and their International Connections. Issue 1 (January 2022) - LEE, RALPH
Abstract : This article traces the history of twentieth-century Ethiopian Orthodox student movements formed in response to modernity, especially the influential Maḫbärä Qəddusan, 'Association of Saints', established in 1991 when Ethiopia's Communist regime fell. It explores parallels in Egyptian and Indian miaphysite Churches; balances the prevailing narrative of explosive Pentecostal growth which has obscured the influence of such movements; provides insight into networks that have stimulated renewal and responses to contemporary challenges through strong engagement with traditional literary and intellectual heritage; and explores training and publications promoting contemporary reflection on this heritage, the revival of important religious practices and the targeting of influential ecclesiastical and public positions.